2018
DOI: 10.1051/matecconf/201820303009
|View full text |Cite
|
Sign up to set email alerts
|

Copper Metal Removal using Sludge Activated Carbon Derived from Wastewater Treatment Sludge

Abstract: In Malaysia, according to perspective sludge production factor (SPF), wastewater treatment plants produces about 5.3 million m3 of sewage sludge annually, most of this sludge are being wasted (unused) in the landfills. This study employed the use of dry activated sludge as low-cost adsorbent for the removal of copper Cu (II) from wastewater. Adsorption of Cu (II) by sludge activated carbon (SAC) was conducted using batch tests. The effect of contact time and adsorbent dosage on the removal of Cu (II)) from was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Abeer et al reported the preparation of AC from apricot stone and its application in removal of Zn + 2 and Al + 3 ions with removal efficiency of 92% [163]. Ebrahim et al designed AC from sewage sludge, applied it for the removal of Cu + 2 ions from water, and found that the designed material showed maximum adsorption capacity of above 50% [164].
Fig.
…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…Abeer et al reported the preparation of AC from apricot stone and its application in removal of Zn + 2 and Al + 3 ions with removal efficiency of 92% [163]. Ebrahim et al designed AC from sewage sludge, applied it for the removal of Cu + 2 ions from water, and found that the designed material showed maximum adsorption capacity of above 50% [164].
Fig.
…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…In a large-scale industrial application of adsorbent in the removal of a desired solute, the quantity or mass of adsorbent is an important factor. A series of adsorption experiments were carried out with different masses of adsorbent at a fixed initial solute concentration to investigate the effect of adsorbent mass on adsorption [20,53].…”
Section: Effect Of Sac Dosagementioning
confidence: 99%
“…Activated carbon is one of the most widely used adsorbents owing to its excellent adsorption properties that can remove a wide range of contaminants. However, despite the efficiency of activated carbons, their uses are limited due to their expensive nature [13,14]. In the last decades, biopolymers have attracted much attention as an eco-friendly alternative for heavy metal removal due to their low cost and high availability [15].…”
Section: Introductionmentioning
confidence: 99%